2012
DOI: 10.1021/ma300034f
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotactic Polyallyltrimethylsilane-Based Stereoregular Diblock Copolymers: Syntheses and Self-Assembled Nanostructures

Abstract: Structurally well-defined stereoregular diblock copolymers composed of syndiotactic polyallyltrimethylsilane (sPATMS) and poly­(methyl methacrylate) (PMMA) were prepared by using an α-bromoester-terminated sPATMS macroinitiator, which was chain extended by MMA using a cuprous halide-based atom transfer radical polymerization (ATRP) system. The α-bromoester-terminated sPATMS macroinitiator was prepared via the esterfication of hydroxyl-capped sPATMS with α-bromoisobutyryl bromide. The hydroxyl-capped sPATMS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 110 publications
1
4
0
Order By: Relevance
“…Initiation and propagation of MMA on the PCHE-BiBB macroinitiator proceeded rapidly within the first 5 h, but complete initiation never occurred even up to 19 h of reaction time (Figure SI-6). Similar issues have been reported for ATRP of MMA with macroinitiator-based systems. , Regardless of the conditions used, all the ATRP products recovered contained unreacted macroinitiator which was affectively removed through Soxhlet extraction (Figure SI-7) with hexanes or pentane to give a small library of PCHE–PMMA samples with low values of molar mass dispersity (Table ). Figure shows overlaid SEC chromatograms for each PCHE–PMMA block copolymer after extraction along with the corresponding PCHE-BiBB precursors as evidence for successful removal of unreacted macroinitiator.…”
Section: Results and Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Initiation and propagation of MMA on the PCHE-BiBB macroinitiator proceeded rapidly within the first 5 h, but complete initiation never occurred even up to 19 h of reaction time (Figure SI-6). Similar issues have been reported for ATRP of MMA with macroinitiator-based systems. , Regardless of the conditions used, all the ATRP products recovered contained unreacted macroinitiator which was affectively removed through Soxhlet extraction (Figure SI-7) with hexanes or pentane to give a small library of PCHE–PMMA samples with low values of molar mass dispersity (Table ). Figure shows overlaid SEC chromatograms for each PCHE–PMMA block copolymer after extraction along with the corresponding PCHE-BiBB precursors as evidence for successful removal of unreacted macroinitiator.…”
Section: Results and Analysissupporting
confidence: 63%
“…The procedure for functionalization of PCHE-OH with BiBB was similar to that described by Lee et al In this case, cyclohexane was used, which caused a majority of the TEA-HBr byproduct to crash out of solution. After completion, the salts were removed by filtration through a 0.45 μm HVHP Millipore membrane.…”
Section: Experimental Detailsmentioning
confidence: 99%
“…The s PMP–PLLA was prepared in two steps. First, hydroxyl-capped s PMP was synthesized by syndiospecific polymerization of 4-methyl-1-pentene conducted in the presence of triethylaluminum (chain transfer agent) using Me 2 C(Cp)(Flu)ZrCl 2 /MAO as a catalyst. The resulting aluminum-capped s PMP was in situ treated with O 2 /H 2 O to provide the hydroxyl-capped s PMP. Second, the s PMP–PLLA was synthesized by ring-opening polymerization of l -lactide using tin(II) octoate as the catalyst and hydroxyl-capped s PMP as the macroinitiator.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the authors reported that both the size and the periodicity of the PDMS domains could be tuned depending on the degree of swelling during solvent vapour annealing [140]. A polyallyltrimethylsilane-block-poly(methyl methacrylate) (sPATMS-b-PMMA) BCP was prepared by using an α-bromoester-terminated sPATMS macroinitiator, which was chain extended by MMA using a cuprous halide-based atom transfer radical polymerization (ATRP) [141] [62]. PLA-b-PDMS is another candidate to obtain small feature sizes since its incompatibility also is larger than that of PS-b-PDMS.…”
Section: (Iii) Other Silicon-containing Block Copolymersmentioning
confidence: 99%